Unsung hero [videorecording (Blu-Ray + DVD)] - Ramsey, Richard (Film director/writer); Betts, Daisy, 1982-; Smallbone, Joel; Smallbone, Joel; Berger, Kirrilee, 1999-; Jackson, Jonathan, 1982-; Black, Lucas, 1982-; Cameron-Bure, Candace, 1976-; O'Quinn, Terry, 1952-; Scott, Hillary, 1986-; McCorkle, Brent; Derango, Johnny, 1980- (Lionsgate, 2024)
Based on a remarkable true story, Unsung Hero follows David Smallbone as he moves his family from Down Under to the States, searching for a brighter future after his successful music company collapses. With nothing more than their seven children, suitcases, and their love of music, David and his pregnant wife Helen set out to rebuild their lives. Helen's faith stands against all odds and inspires her husband and children to hold onto theirs. With their dreams on hold, David and Helen begin to realize the musical prowess in their children, who would go on to become two of the most successful acts in Inspirational Music history.